130 Cytomegalovirus-Induced Glomerular Vasculopathy in a Renal Allograft With Subtle Cytopathic Features. (11th January 2018) - Sakhi, Ramen; Qu, Hong; Khurram, Muhammad
Abstract: Cytomegalovirus (CMV) complicates up to 40% of all renal transplantations. Graft loss occurs 10%-20% of the time. The most commonly occurring manifestation of CMV infection is tubulointerstitial nephritis, which is characterized by nuclear and cytoplasmic inclusions within tubular epithelial cells. We describe a very rare case of CMV-induced glomerular vasculopathy without the classic microscopic presentation of obvious intranuclear inclusions. A 17-year-old male renal transplant recipient from a related living donor three months earlier who was on immunosuppressants was discovered to have a rising creatinine level. He underwent a renal biopsy, which revealed glomerular and rare peritubular capillary endothelial cells involved by CMV. Interstitial inflammation, tubulitis, and arteritis were absent. CMV tissue involvement was confirmed by immunohistochemical stains for CMV and by electron microscopy. C4d stains were negative in peritubular capillaries. The patient responded well to antiviral medication. CMV nephropathy can manifest as glomerular vasculopathy, glomerulonephritis, or most commonly tubulointerstitial nephritis. In previously reported cases, patients presented with CMV-induced glomerular vasculopathy on average 3 to 4 months post renal transplantation. The major morphologic changes of CMV-induced glomerular vasculopathy consist of enlargement or necrosis of endothelial cells within glomeruli with absence of tubulointerstitial changes. The classic pattern of cherry red, intranuclear inclusions with a halo is not always present in endothelial cells in these cases. Instead, the CMV-infected endothelial nucleus may be blurred, filling up the capillary lumen resembling microthrombi. Given the rarity of this entity and subtle changes which are easily overlooked, it is necessary to perform CMV stains in all transplant biopsies with in situ hybridization or immunohistochemistry.